Author Correction: Increased human and economic losses from river flooding with anthropogenic warming. Issue 11 (November 2018) - Dottori, Francesco; Szewczyk, Wojciech; Ciscar, Juan-Carlos; Zhao, Fang; Alfieri, Lorenzo; Hirabayashi, Yukiko; Bianchi, Alessandra; Mongelli, Ignazio; Frieler, Katja; Betts, Richard; Feyen, Luc
In the version of this Letter originally published, the affiliation for Yukiko Hirabayashi was mistakenly given as 'Institute of Industrial Science, The University of Tokyo, Bunkyō, Japan'. It should have read 'Department of Civil Engineering, Shibaura Institute of Technology, Tokyo, Japan'. This has now been corrected.